The remittance behaviour of Kenyan sibling migrants - Farai Jena (IZA Journal of Migration, 2016)
This paper examines the remittance behaviour of multiple-sibling migrants and the motivations of Kenyan siblings in sending remittances to their household of origin. The presence of other siblings is found to decrease the probability of remitting but has no effect on the amount sent. The volume of remittances sent by other siblings is also found to have no statistically significant effect on the amount sent by a sibling. Thus, the evidence obtained offers some mild, though not unambiguous, support for sibling remittances being driven by altruistic as well as independent motives.
Keywords: B21; D19; J69; 330; Siblings; Remittance behaviour; Kenya